Financial Economics: Array - Collective Authors (Acta Universitatis Danubius. Œconomica, 2021)
Kosovo’s sluggish economic growth and financial market developments are two main reasons for conducting the analysis of banking system interest rates in Kosovo. It has been always considered that increase in the number of banks will in turn result in higher competitiveness; however this did not happened and the interest rates have only seen increase. As a result of this situation, poor access to loans continues to severely hamper the household and business economic activities in Kosovo. Despite rapid development of banking sector in Kosovo that was built since 2000 and which is considered as one of the most successful ones in Kosovo’s economy, the impact of micro policies and governmental policies, including the high interest rates, have reflected in sluggishness of entrepreneurial initiatives. Irrespective of a considerable number of banks operating today in Kosovo (10 banks), this sector remains quite concentrated, since around 90% of total assets, more than 88% of deposits and around 80% of loans are concentrated in three largest banks with foreign capital.